Development and Validation of a Functional Health Literacy Instrument in the Philippines - Ma. Carmen C. Tolabing; Kim Carmela D. Co; Martin Aaron M. Mamangon (International Journal of Public Health Science (IJPHS), 2022)
Functional Health Literacy (FHL) involves skills in writing, reading, oral expression, comprehension, and numerical calculations to successfully function and complete health-related tasks. This study aimed to develop and validate an instrument for measuring FHL in the Philippines using a mixed-method design. FHL-5TEST is an instrument consisting of five questions developed in consultation with local experts, translated to major Philippine languages, and underwent translation analysis, pretesting, cultural adaptation, and validation.. A cross-sectional study was conducted in a random sample of 15-70-year-old Filipino residents to validate the instrument. The FHL-5TEST demonstrated high internal consistency, with a Cronbach’s alpha of 0.7690. Across different cut-off values, the sensitivity and specificity of the instrument in detecting limited FHL ranged from 60.9% to 86.0% and from 61.6% to 97.2%, respectively. The study demonstrated that the FHL-5TEST is a valid and reliable instrument to measure functional health literacy in the Philippines.